Organisms associated with ventilator associated pneumonia (VAP) in intensive care units (ICU) - Selina, Farhana; Talha, Khandaker Abu; Islam, Amirul; Hasan, Zahidul; Hyder, Masum; Selvapandian, S (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: Organisms associated with ventilator associated pneumonia (VAP) in intensive care units (ICU). Aims and objectives: To identify the organisms associated with ventilator associated pneumonia and to compare our study with other international studies. Methods: This observational study on VAP was conducted in different ICU of Square Hospital Limited during the two years. Any ventilated patient who developed fever or respiratory distress was clinically assessed by attending physician. This includes time of developing fever after intubation, physical examination findings (auscultation finding, pattern of temperature) and X-ray findings. On the day of onset of fever or respiratory distress, tracheal aspiration was done and the aspirated fluid was sent to microbiology lab. for culture and sensitivity test. If patient was designated to be suffering from VAP all relevant information was documented in a structured questionnaire. Results: In our study we found 15 organisms responsible for VAP. Among these common organisms were pseudomonus(35%), acinetobacter(29%), klebsiella(16%), MSSA (10%), MRSA(9).Total number of cases was 79. Among these 21 patients expired which was 26.5% of the whole series. Total 534 patients died in this hospital during this 2 years. Death for VAP was 4% of the total death of the hospital. Conclusion: Pseudomonas was the most commonest among identified organisms with ventilator associated pneumonia and medicine department having maximum number of VAP patients. To compare our results with those of international studies we found similarity in organisms, primary diagnosis and mortality. DOI: http://dx.doi.org/10.3329/jbsa.v22i2.18146 Journal of BSA, 2009; 22(2): 72-77